Knowledge of critical care nurses about the process of brain death diagnosis - Agnes Claudine Fontes de la Longuiniere; Márcio Pereira Lobo; Paula Lacerda Leite; Rita de Cássia Santos Barros; Alécia Nunes Souza; Sheylla Nayara Sales Vieira (Universidade Federal do Ceará, 2016)
Objectives: to understand the knowledge of critical care nurses about the process of brain death diagnosis. Methods: qualitative study conducted with nurses who work in the Intensive Care Unit. Data were collected through interviews and analyzed based on the Discourse of the Collective Subject technique. Results: as regards the concept of brain death, there was predominance of lack of brain activity. Regarding the procedures to confirm the diagnosis of brain death, the speeches brought up two stages composed of clinical tests and follow-up protocol. As for the nurses' role in this process, the statements highlight the importance of informing the Intra-Hospital Committee of Organ and Tissue Donation and assisting the donor. Conclusion: participant nurses presented knowledge on the diagnosis of brain death and the role of nurses as part of the multidisciplinary team, revealing the importance of the performance of these professionals for achieving the organ donation and the need for constant improvement.